Rapid diagnoses at the breast center of Jeroen Bosch Hospital: a case study invoking queueing theory and discrete event simulation. Issue 1 (1st March 2017) - van de Vrugt, Maartje; Boucherie, Richard J.; Smilde, Tineke J.; de Jong, Mathijn; Bessems, Maud
Abstract: When suspected tissue is discovered in a patient's breast, swiftly available diagnostic test results are essential for medical and psychological reasons. The breast center of the Jeroen Bosch Hospital aims to comply with new Dutch standards to provide 90% of the patients an appointment within three working days, and to communicate the test results to 90% of the patients within a week. This case study reports on interventions based on a discrete time queueing model and discrete event simulation. The implemented interventions concern a new patient appointment schedule and an additional multi-disciplinary meeting, which significantly improve in both the appointment and diagnostics delay. Additionally, we propose a promising new patient schedule to further reduce patient waiting times and staff overtime and provide guidelines for how to achieve implementation of Operations Research methods in practice.